Revolutionizing Learning for Emotional Growth: A Bibliometric Review of Research on Innovative Pedagogies and Student Well-being - Septiana, Nila Zaimatus; Rahmawati, Novi Rosita; Puspitasari, Intan Nuyulis Naeni; Laili, Ummiy Fauziyah (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This study presents a bibliometric analysis of research on innovative pedagogy and student emotional well-being from 2015 to 2025, based on 2,613 articles extracted from the Scopus database. The study aims to map publication trends, leading authors, and emerging themes related to this topic. The methodology employs bibliometric analysis using RStudio and the Bibliometrix R package to process the Scopus data. The results indicate a significant increase in publications since 2020, with key topics including Social-Emotional Learning (SEL), gamification, and technology-mediated learning. Co-citation analysis reveals that theories such as Social Learning and Experiential Learning dominate the literature. The study also identifies a disparity in research contributions between developed and developing countries, with the United States and the United Kingdom leading in publications. The findings suggest the need for further inclusive research based on diverse cultural contexts and emphasize the importance of integrating social-emotional well-being into educational curricula to create more holistic and inclusive learning environments